Factors Associated with Herbs Clinic Utilization in Patients with Diabetes Mellitus in Tawangmangu, Central Java - Agus Triyono; Bhisma Murti; Hanung Prasetya (Journal of Health Promotion and Behavior, 2020)
Background: The utilization of herbs increased for complementary medicine and alternative chronic diseases including Diabetes Mellitus (DM). There are many factors that affect patients with Diabetes Mellitus to utilize herbal clinic. This study aimed to analyze the effects of age, gender, education, occupation, income, marital status, family support, knowledge of herbs, attitude towards herbs, and duration of Diabetes Mellitus on herbs clinic utilization.Subjects and Method: This was a cross-sectional study. This study was conducted in Tawangmangu, Central Java, from January to March 2020. A sample of 200 DM patients aged 15-60 years who were examined at Jamu Research House (rrj) or community health center in Tawangmangu. The sample was collected by purposive sampling. The dependent variable was herbs clinic utilization. The independent variables were sex, age, education, occupation, income, marital status, family support, knowledge of herbs, attitude towards herbs, and duration of DM. The data were collected by questionnaire and analyzed by path analysis run on Stata 13.Results: Herbs clinic utilization was directly increased by positive attitude towards herbs (OR= 5.37; 95% CI= 2.49 to 11.60; p<0.001), duration of DM ≥5 years (OR= 2.02; 95% CI= 1.00 to 4.07; p=0.040), high family income (OR= 2.67; 95% CI= 1.41 to 5.01; p= 0.003), good family support (OR= 1.93; 95% CI= 0.96 to 3.87; p= 0.063), age ≥35 years (OR= 1.45; 95% CI= 0.27 to 7.19; p= 0.666), female (OR= 0.59; 95% CI= 0.31 to 1.12; p= 0.108), and married (OR= 0.64; 95% CI= 0.26 to 1.61; p= 0.343). Herb clinic utilization was indirectly affected by knowledge of herbs, education, and occupation.Conclusion: Herbs clinic utilization is directly increased by positive attitude towards herbs, duration of DM ≥5 years, high family income, good family support, age ≥35 years, female, and married. Herb clinic utilization is indirectly affected by knowledge of herbs, education, and occupation.Keywords: herbs clinic utilization, Diabetes Mellitus, path analysisCorrespondence: Agus Triyono. Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir.Sutami No 36 A, Surakarta 57126, Central Java,Indonesia. Email: agustriyono_21@yahoo.com. Mobile: +6281329038465.Journal of Health Promotion and Behavior (2020), 05(03): 147-156https://doi.org/10.26911/thejhpb.2020.05.03.01